The application of Failure Mode Effects Analysis in the long supply chain – A case study of ultra filtrated milk cheese. (August 2022) - Aleksic, Biljana; Djekic, Ilija; Miocinovic, Jelena; Miloradovic, Zorana; Memisi, Nurgin; Smigic, Nada
Abstract: A long food supply chain is a complex food path from producer to consumer in which multiple participants are involved, and in which various failures for both food safety and food quality can be identified. The purpose of this study was to apply the Failure Mode Effects Analysis (FMEA) technique to analyze various aspects of industrial production of cheeses produced from ultra-filtered milk (UF cheeses). Data were obtained from three dairy farms, three big dairy companies, and three trade organizations located in Serbia. Risk Priority Numbers (RPN) were calculated to rank the risk of failures identified at each production step. The obtained results showed that the greatest risks are related to the production at the dairy farms as well as the reception of raw milk at dairy processing plants, being failures that are not noticed at the primary production step. They have been covered by dairies implemented HACCP based food safety management system, which significantly reduces the risk level. The applied FMEA methodology indicates the importance of preventive food safety measures within the whole chain. Also the role of the state in improving the quality of raw milk should be emphasized. The results of this study can be used to improve the status of dairy farms in terms of animal health and welfare, but also for the identification and assessment of most common failures at dairy processing plants, and transportation and cold storage phase during retail. Highlights: FMEA analysis was applied for risk assessment in long UF cheese supply chain. Field research was conducted at primary production, dairy processing and trade steps. Production of raw milk at farms and reception to dairies posed the greatest risks. National raw milk quality control should be emphasized.